Institutional Perspectives On Intangible Assets In Performance Measurement: Toward A Conceptual Framework Of Value Creation - Dwi Cahya Widiyanata; Endah Wulan Safitri (CV Edujavare Publishing, 2026)
This study aims to develop a conceptual framework for measuring organizational performance by integrating institutional theory with the management of intangible assets. Traditional performance measurement systems primarily emphasize financial indicators and often fail to capture the strategic value created through knowledge, organizational culture, innovation, human capital, and stakeholder relationships. Using a qualitative conceptual approach based on an extensive review of the literature, this study synthesizes previous theoretical and empirical findings to explain how institutional pressures influence the recognition, management, and utilization of intangible assets in organizational value creation. The proposed framework highlights the interaction between institutional environments, organizational capabilities, and intangible resources as determinants of sustainable organizational performance. The model also emphasizes that legitimacy, governance, and strategic alignment strengthen the contribution of intangible assets to long-term competitiveness. This conceptual framework offers theoretical implications for extending institutional theory in performance measurement and provides practical guidance for organizations seeking to improve strategic decision-making through more comprehensive and value-oriented performance evaluation systems.